2001
DOI: 10.1182/blood.v97.4.1079
|View full text |Cite
|
Sign up to set email alerts
|

Cell-surface heparan sulfate proteoglycan–mediated regulation of human neutrophil migration by the serpin antithrombin III

Abstract: The serpin antithrombin III (AT III) is reported to have hemostasis-regulating and anti-inflammatory properties. To determine its ability to influence thrombin-independent leukocyte responses, the direct effects of the AT III concentrate Kybernin P and a monoclonal antibody-purified AT III on neutrophil migration were studied. Chemotactic activity of human neutrophils isolated from the blood of healthy donors was determined in modified Boyden microchemotaxis chambers, and binding studies were performed accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 41 publications
6
105
0
7
Order By: Relevance
“…Recently, results of in vitro experiments raised the possibility that AT might inhibit leukocyte activation directly. Dunzendorfers et al 13 reported that AT directly inhibited neutrophil chemotaxis by binding to the cell surface-heparan sulfate glycosaminoglycans. Souter et al 14 demonstrated that AT directly inhibited interleukin-6 production by monocytes stimulated with lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, results of in vitro experiments raised the possibility that AT might inhibit leukocyte activation directly. Dunzendorfers et al 13 reported that AT directly inhibited neutrophil chemotaxis by binding to the cell surface-heparan sulfate glycosaminoglycans. Souter et al 14 demonstrated that AT directly inhibited interleukin-6 production by monocytes stimulated with lipopolysaccharide.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In contrast to these reports, AT has been demonstrated to inhibit leukocyte activation directly. [13][14][15] These observations suggest that anti-inflammatory effects of AT may be mediated mainly by its direct inhibitory properties on leukocyte activation.…”
Section: Introductionmentioning
confidence: 91%
“…The proposed mechanism of action is reduced production of prostacyclin by endothelium upon interaction of AT-III with cell surface heparan sulfate proteoglycans (14)(15)(16). In the absence of endothelium, AT-III ligates with heparan sulfate proteoglycans of leukocytes and affects their migratory responses directly via syndecan-mediated signaling mechanisms (17)(18)(19)(20). This suggests that a different mechanism exists by which leukocyte activation may be attenuated with AT-III during cardiopulmonary bypass.…”
Section: Resultsmentioning
confidence: 99%
“…17 In various experiments, neutrophil migration was tested toward phPC, ArhPC, AphPC (0.1 pg/mL to 10 g/mL), interleukin-8 (IL-8) (1 nM), formyl-Met-Leu-Phe (fMLP), C5a (both 10 nM), or AT (1 U/mL). For deactivation, neutrophils were incubated for 20 minutes at various concentrations of PC or APC (0.1 pg/mL to 10 g/mL).…”
Section: Leukocyte Chemotaxis Assaymentioning
confidence: 99%